How Did You Sleep Tonight? The Relevance of Sleep Quality and Sleep–Wake Rhythm for Procrastination at Work - Maier, Tabea; Kühnel, Jana; Zimmermann, Beatrice (Frontiers in Psychology, 2022)
Recent studies have highlighted the relevance of sleep with procrastination at work. Procrastination at work is defined as the irrational delay of the initiation or completion of work-related activities. In line with recent studies, we offer a self-regulation perspective on procrastination. We argue that procrastination is an outcome of depleted self-regulatory resources and that the restoration of self-regulatory resources during high-quality sleep at night would prevent procrastination. Aims: In an attempt to further develop this line of research, the current study aimed to achieve a broader understanding of the relevance of sleep and circadian rhythm for procrastination. Therefore, we explored the effect of sleep quality on procrastination for different chronotypes. We also considered the shift to daylight saving time as a phenomenon that aggravates circadian misalignment and thereby later chronotypes’ dependence on high-quality sleep. Specifically, we hypothesized that compared to employees with an earlier chronotype (morning type), employees with a later chronotype (evening types) are more dependent on good sleep at night to prevent procrastination the next day. This effect would be especially pronounced after the shift to daylight saving time. Methods: For this repeated-measures study, participants were 101 full-time employees. They completed a general questionnaire and day-specific questionnaires on the Monday before and the Monday following the shift to daylight saving time. Results: The multilevel analyses showed that employees procrastinated less on days following nights during which they slept better and that later chronotypes (evening types) experienced more procrastination than earlier chronotypes (morning types). Our findings also supported the hypothesis that the relationship between sleep quality and procrastination is stronger for later chronotypes compared to earlier chronotypes on the Monday following the shift to daylight saving time. In other words, the lower the sleep quality of later chronotypes during the previous night, the more they procrastinated on the Monday following the shift to daylight saving time. Discussion: Our findings further corroborate the existing findings on the relevance of sleep and chronotype for well-being and performance at work.